Principal moments of a multipole expansion to quantify the magnetic nanoparticle distributions in arteries - Wiekhorst, Frank; Haberkorn, W.; Steinhoff, Uwe; Lyer, Stefan; Alexiou, Christoph; Baer, M.; Trahms, L. (Biomedizinische Technik, 2012)
We present a multipole based approach to model linearly extended nanoparticle distributions in an artery and to reconstruct these distributions from their distant magnetic field. The multipole moments of a spherical harmonic multipole expansion are evaluated for an arbitrary nanoparticle distribution in an artery magnetized perpendicular to its axis. It is shown that each multipole order is determined by only one principal multipole moment. All other possible moments of the respective multipole order can be related to the principal moment and carry the same information about the linear model. Consequently each multipole order is characterized by a typical field pattern. For both homogeneous and inhomogeneous nanoparticle distributions in the artery model the distribution parameters are determined from the principal multipole moments. © 2012 by Walter de Gruyter Berlin Boston.
CRIS-Team Scopus Importer:2022-06-27